Commitment and resilience of public and private high school teachers in Yogyakarta - Titik Muti'ah; Indriyati Eko Purwaningsih; Juni Sungsang Prakosa; Jhonnel J. Abalajon (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2023)
Teaching is one of the noble professions and has high complexity, requiring good resilience in school and class. The purpose of this study is to determine the relationship between the commitment and resilience of public and private high school teachers. This is quantitative research with 43 subjects (25 public high school teachers and 18 private high school teachers) in the city of Yogyakarta, obtained by incidental sampling technique. The preparation of the scales and the implementation of a valid and reliable scale trial were also carried out. There are 27 items on the resilience scale with a reliability value of .929 and a scale of teacher commitment behavior with 22 items reliability value of .873. The analysis technique used is Person Correlation and independent sample t-Test with SPSS program. The results showed that there was a positive relationship between commitment and resilience subjects with a correlation coefficient value of .737, with significance (p) 0.000. While the difference test shows that there is a differentiation in the resilience of teachers in private schools with public schools, with a significance of p .000. Although there are differences in resilience, the data description shows a high level of commitment and resilience of teachers above 75%, with 62% working period over 11 years, the subject's employment status is 44% as contract teachers, 40% ASN, and 16% permanent teachers. The researchers recommended conducting a teacher resilience knowledge, skills and attitude in designing a Teacher Resiliency Training Plan or Design.